2015
DOI: 10.3168/jds.2015-9310
|View full text |Cite
|
Sign up to set email alerts
|

Methyl-coenzyme M reductase A as an indicator to estimate methane production from dairy cows

Abstract: The evaluation of greenhouse gas mitigation strategies requires the quantitative assessment of individual methane production. Because methane measurement in respiration chambers is highly accurate, but also comprises various disadvantages such as limited capacity and high costs, the establishment of an indicator for estimating methane production of individual ruminants would provide an alternative to direct methane measurement. Methyl-coenzyme M reductase is involved in methanogenesis and the subunit α of meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…Comparing the mcrA gene abundance between the low and high emission groups (170% increase) resulted in a highly significant difference ( S2 Fig ). An association between mcrA gene abundance and methane emissions has been reported in dairy cattle [ 27 ] and sheep (at the transcriptomic level) [ 28 ], whilst this gene is recommended for monitoring the process performance of anaerobic digesters [ 29 ]. Another identified archaeal gene was formylmethanofuran dehydrogenase subunit B ( fmdB ), which is also involved directly in methanogenesis and catalyses the reversible reduction of CO 2 and methanofuran via N-carboxymethanofuran (carbamate) to N-formylmethanofuran, the first and second steps in the methanogenesis from CO 2 [ 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Comparing the mcrA gene abundance between the low and high emission groups (170% increase) resulted in a highly significant difference ( S2 Fig ). An association between mcrA gene abundance and methane emissions has been reported in dairy cattle [ 27 ] and sheep (at the transcriptomic level) [ 28 ], whilst this gene is recommended for monitoring the process performance of anaerobic digesters [ 29 ]. Another identified archaeal gene was formylmethanofuran dehydrogenase subunit B ( fmdB ), which is also involved directly in methanogenesis and catalyses the reversible reduction of CO 2 and methanofuran via N-carboxymethanofuran (carbamate) to N-formylmethanofuran, the first and second steps in the methanogenesis from CO 2 [ 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…We conducted a meta-analysis on the impact of increasing corn silage relative to the other silages following the methodology described in Alvarez-Fuentes et al (2016). Forty-seven treatment means of enteric methane emission measurements from lactating cows fed corn silage (17.7%-53.3% of DM) and grass silage (5.5%-53.3% of DM)-based diets in the US and Europe (Dohme et al 2004;Hindrichsen et al 2006;O'Neill et al 2011;van Zijderveld et al 2011avan Zijderveld et al , 2011bHollmann et al 2012Hollmann et al , 2013Brask et al 2013;Haque et al 2014;Reynolds et al 2014;Aguinaga Casañas et al 2015;Livingstone et al 2015;van Gastelen et al 2015) were used. The results indicated that the ratio of corn silage to grass silage (CS:GS) (ranging from 0.5 to 7.0 with a mean of 3.2) was negatively associated (P = 0.007) with CH 4 production (g cow −1 d −1 ) and explained 15% of variability in the treatment means.…”
Section: Increasing Corn Silage Content In the Dietmentioning
confidence: 99%
“…Methanogenic microbiota utilize the released hydrogen to reduce CO 2 yielding in the formation of CH 4 1 . Accordingly, the ruminal acetate or the (acetate + butyrate) : propionate ratio is highly related with daily CH 4 emission (g/d) or CH 4 yield expressed as g per unit of dry matter intake (g/kg DMI) 2 3 . In the post-absorptive metabolism of dairy cows, propionate is primarily used for hepatic gluconeogenesis, whereas acetate is activated to form acetyl-CoA serving as the main energy-providing substrate for the host.…”
mentioning
confidence: 99%